Power and explosiveness: first step(s) - Stone, M. H.; Sato, K. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Power (along with Impulse) is arguably the most import characteristic for an athlete to develop. Power (particularly peak power) has strong relationships with sports performance such as lifting, throwing, sprinting, jumping and agility. Development of power is best accomplished by a progressive sequence that is characterized by successive phases that increased work capacity, muscle cross-section area, maximum strength and task specific power. Furthermore, evidence indicates that for power development, weaker athletes benefit as much or more from the development of strength through basic strength training than from power training.